Staff perceptions of the effects of malodours from toilets at two schools in Gauteng Province, South Africa (The Journal of Geography Education in Africa, 2022)
In any school system, sanitary facilities can have a major effect on the productivity of staff and students, thus safe, adequate sanitation is essential to the academic programme. This study is part of a pilot project to determine the perceptions staff have of the effects of malodours from toilets on productivity and morale, at two schools. One school (School A) is located on the periphery of an urban area and had a septic tank system with inadequate toilet maintenance. The other school (School B) was in a well-established urban area with a flush latrine system, connected to municipal sewage pipes. Through a self-administered questionnaire we determined that School A had a very poor sanitation system that produced unbearable malodours that affected health, productivity and morale at the school, whereas School B had a healthy, well-maintained sanitation system that produced little odour. The malodour at School A had a negative effect on pupil attendance and staff morale at the school. The significant finding of the research was that all staff who participated indicated that malodours from either a flush latrine or a septic tank system could affect productivity of staff and students in the school environment.
Keywords: Olfactory perception; school toilet odours; flush toilets; pit latrines